The Existence of Pesantren Culture as an Indonesian Islamic Educational Institution - Djuwairiyah, Djuwairiyah; Jamil, Asyraf Isyraqi; Kadir, Fakhrul Adabi Abd (Jurnal Pendidikan Islam Indonesia, 2023)
Pesantren is an Islamic educational institution which its existence has been legalized in accordance with the needs and along with the development of times. The students’ principles of ethics, morality, religion, and independence are strengthened, which distinguish pesantren from other educational institutions. These goals can be compared to the range of scientific-technological knowledge and technical abilities which are needed to develop religious scientists. Pesantren for Indonesian Muslims surely become the focus of scientific and technological progresses, which is not only become a traditional Islamic educational institution that only focuses on religious affairs.